Prevalence and Distribution of Impacted Teeth in a Libyan Subpopulation: A Retrospective Study at the LIMU Dental Centre - Mervet El-Zuki; Boshala, Farag; Ahmad , Okba; Salah, Ihab; Maher, Suliman (AlQalam Journal of Medical and Applied Sciences, 2025)
This observational, cross-sectional, retrospective study investigated the prevalence and distribution of impacted teeth among Libyan patients attending the Dental Centre at the Libyan International Medical University (LIMU) between May 2021 and February 2023. Out of 1553 panoramic radiographs, 1113 met the inclusion criteria. Impacted teeth were identified in 610 patients (54.8%), with nearly equal distribution between the upper (27.8%) and lower (27%) arches. The upper left region showed the highest frequency of impaction (14.6%). Statistical analysis revealed a significant association between age and tooth impaction (p ≅ 0.00), particularly among patients under 30 years, while gender showed no significant influence (p > 0.05), except for the upper right arch (p = 0.017). The most commonly impacted teeth were the upper right third molars and upper canines. The study concludes that age and tooth location are key factors in impaction prevalence, whereas gender plays a minimal role.